Uso da floculação de tensoativo para remoção de corantes: Avaliação da cinética e concentração. - Evangelista, Maria Neudna Diniz (Universidade Federal Rural do Semi-Árido, 2018)
Contamination of the effluents is becoming a worrying phenomenon and it is one of the main problems faced by the industry. The organic compounds that are discarded are harmful to fauna and aquatic flora and may cause irreparable damage. In this way, an adequate treatment of the effluent is necessary to reduce the concentration of these substances released into the environment. This work proposes the use of ionic flocculation to remove three pollutants models, namely: Solophenyl Black FR, Brown Solophenyl RLN and Yellow HP. Initially, the surfactant is produced from sunflower oil, where it is added to an aqueous medium, thereafter the calcium is added to form flocks, which in turn produces an adsorbent surface capable of attracting the dye molecules. The samples are centrifuged and effluents are obtained with lower concentrations of pollutants. In this work the parameters were evaluated surfactant concentration and the operating time that comes from the study of chemical kinetics. The tests showed that among the dyes tested, it was possible to observe that the solophenyl black FR dye presented the highest efficient with removal of 94%, using a surfactant concentration of 1000 ppm, indicating that ionic flocculation is an alternative to remove organic compounds from the water.
Keywords: Tensoativo; Corante; Efluente têxtil; Eficiência de remoção; Tensoactive; Dyes; Textile effluents; Removal efficiency; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA